Seroprevalence and associated risk factors of trichinellosis and T. solium cysticercosis in indigenous pigs in Hoa Binh Province, Vietnam - Trang Thi-Huyen Le; Nga Vu-Thi; Sinh Dang-Xuan; Hung Nguyen-Viet; Phuc Pham-Duc; Luong Nguyen-Thanh; Ngoc Pham Thi; Noh, J.; Mayer-Scholl, A.; Baumann, M.; Meemken, D.; Unger, Fred (MDPI, 2022)
Trichinellosis and cysticercosis remain challenges to human health and animal productivity worldwide, especially in developing countries. While information on the occurrence of both diseases is infrequent, they are endemic in parts of Vietnam and mainly related to indigenous pigs kept by ethnic minorities. This study aimed to determine the seroprevalence and risk factors of both diseases in indigenous pigs and explore the perception and awareness of both human and pig trichinellosis and cysticercosis of pig farmers. A total of 352 pig sera samples from 131 holdings were collected and analyzed using ELISA antibody tests in six communes in the Da Bac districts of Hoa Binh province, Vietnam. A survey was conducted with representatives from these households to understand the knowledge and perspective on food-borne parasitic diseases. Overall, the seroprevalence of trichinellosis and T. solium cysticercosis was 13.6% (95% CI 10.2–17.7) and 1.7% (95% CI 0.6–3.7), respectively. The seroprevalence of trichinellosis was significantly higher in female and older pigs. Risk perception and knowledge of interviewed people on both human and pig trichinellosis and cysticercosis of pig farmers was poor. Risky practices, including free roaming of pigs and eating undercooked or fermented pork, were observed. Educational and awareness campaigns aligned with further research on feasible practice changes are critical to addressing these issues.